EXAMINING NON-VERBAL COMMUNICATION AND BODY LANGUAGE IN ATTAR NEYSHABOURI'S MUSIBAT-N?MEH - Roghayyeh norouzi ganjabad; Abdullah Tolouei Azar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The role of communication in shaping the integrity of social interaction of societies is important. Communication is the exchange of messages between sender and receiver with maximum impact. Thinking on the communication methods of individuals in a society explains verbal communication and non-verbal indicators. Verbal communication is formed by relying on a tool called "language", while non-verbal communication is formed by using various factors such as body organs, facial expressions, spatial and temporal factors, environmental factors, paralinguistic components, mental and physical states, and symbols help to communicate between people. This method, which is more reliable than the verbal method and the transmission of the message is done quickly, has many reflections in Persian literature texts. Considering the fact that in literary-mystical texts the most use of non-verbal factors of communication emerged, it can be said that mystical poets, in their works, have reflected wide and deep mystical concepts with the help of non-verbal communication components. Musibat-N?meh is one of the best mystical texts that Attar Neyshabouri expressed some of his mystical thoughts by using non-verbal communication capacities. The present research has examined the prominent types of non-verbal characteristics in the Musibat-Nameh and after extracting the verses that - including non-verbal cases of communication - has classified, analyzed and deciphered them. Reflection on the obtained statistics shows how effective this type of communication is in conveying mystical concepts and Attar, with full knowledge of their function, has introduced wide meanings of the world of mysticism into Persian poetry.